2022
DOI: 10.3390/cryst12020222
|View full text |Cite
|
Sign up to set email alerts
|

Bi2Te3/Graphene Heterostructure as the Saturable Absorber for ~1.0 μm Passively Q-switched Solid State Pulsed Laser

Abstract: Due to the tunable nonlinear optical properties of the Bi2Te3/graphene heterostructure, stable solid state pulsed lasers based on the Bi2Te3/graphene saturable absorber have attracted intensive attention. In this work, the Bi2Te3/graphene heterostructure with good nonlinear absorption characteristics was synthesized by a self-assembly solvothermal route, and the optical saturable absorption properties of the saturable absorber were investigated. Owing to the large modulation depth of Bi2Te3 nanosheets and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…This behavior suggests that the ultraslow hole dynamics in the 3D TI Bi 2 Se 3 can be controlled by the thickness of the MgF 2 layer, similar to how it occurs at the Si/SiO 2 interface [15]. Finally, we concluded that the observed dynamics of long-lived holes in the 3D TI Bi 2 Se 3 coated with a thin MgF 2 layer can be applied for designing new thin-film quantum materials that are promising for modern optoelectronics and optospintronics [55][56][57][58], also for metal-oxide-semiconductor field-effect transistor technology [59][60][61][62].…”
Section: Introductionmentioning
confidence: 51%
“…This behavior suggests that the ultraslow hole dynamics in the 3D TI Bi 2 Se 3 can be controlled by the thickness of the MgF 2 layer, similar to how it occurs at the Si/SiO 2 interface [15]. Finally, we concluded that the observed dynamics of long-lived holes in the 3D TI Bi 2 Se 3 coated with a thin MgF 2 layer can be applied for designing new thin-film quantum materials that are promising for modern optoelectronics and optospintronics [55][56][57][58], also for metal-oxide-semiconductor field-effect transistor technology [59][60][61][62].…”
Section: Introductionmentioning
confidence: 51%
“…[100] In the same year, Sun et al chose the hydrothermal method to prepare Bi 2 Te 3 /graphene heterostructure by a self-assembly solvothermal method. [68,101] They first synthesized graphene oxide (GO) with the improved Hummers method, [102] and fabricated Bi 2 Te 3 /graphene heterostructure. The hydrothermal method is promising and has been widely used in large-scale preparation of heterostructure materials.…”
Section: Hydrothermal Methodsmentioning
confidence: 99%
“…Recently, scientists fabricated the bismuth telluride/graphene (Bi 2 Te 3 /graphene) heterostructure, whose exciton time was short and absorption was strong. [ 68 ] Heterostructure materials are prepared by the approach of mechanical transfer and chemical growth, realizing atomic‐level connections between different materials. Magnetron sputtering deposition (MSD) and liquid phase exfoliation (LPE) are two common methods of mechanical transfer, by both of which layered materials can be obtained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remarkable electrical, thermal, mechanical, optical, and long electron mean free paths properties of graphene make it compelling for various engineering applications [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%